Z katalogu zadań pamięcioznawczych - Chlebda, Wojciech (Stylistyka, 2019)
The author gives a concise review of the achievements of memory studies, especially Polish ones, focusing the attention on the new sub-discipline of knowledge, namely linguistic memory studies. After recalling the assumptions of his own concept of “linguified memory,” the author formulates five complex tasks which, in his opinion, are now faced by linguists dealing with memory studies. They are determined by the following: (1) the need for metamemory scientific arrangements; (2) the need for description and classification of linguistic memory exponents; (3) the need for a systemic approach to linguistic memory exponents, i.e. their analysis in clusters (constellations) allowing mapping of collective memories; (4) the need for linguistic research on collective oblivion; (5) the need to search for locations of collective memories/oblivions in order to answer the question of the possibility of transnational (Slavic, European, global) memory/oblivion.